REVIEWING SPECIFIC FEATURES OF MONITORING MARITIME STUDENTS’ LEARNING OUTCOMES - KUZMENKO, Vasyl; KUTSENKO, Iryna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. Maritime education is one of the key factors for the stable development of the state. The fundamental task of Maritime Education and Training institutes is effective seafarer`s education in a way that they acquire applicable knowledge, skills and competencies. Such results cannot be done without monitoring of students` learning outcomes. Comparing to other institutions maritime education and training institutions have special peculiarities of monitoring students` learning outcomes which should be review for better understanding of this process. Purpose. The aim of the thesis is to describe the main peculiarities of monitoring maritime students` learning outcomes. Results. The creation and implementation of quality management systems in maritime higher education institutions is provided in accordance with international standards, ISO 9002: 2000 quality standards. However, the training of marine specialists is also guided by the requirements of the International Maritime Organization, such as Standards of Training, Certification and Watchkeeping for Seafarers Convention (STCW) an IMO Model Courses for operational and management levels, which states, that one of the effective ways to reduce the risks associated with human error in the vessel navigation is to implement the highest standards of training, certification and competence of seafarers into the education process. The references made by STCW Convention to quality standards are related to quality assurance: all training; assessment of competence; certification; endorsement; revalidation activities. All the above have to be continuously monitored through a quality standards system to ensure the achievement of defined objectives, including those concerning the qualifications and experience of instructors and assessors. In keeping with the requirements of IMO – STCW and, Vocational Standards applied by maritime nations for higher qualifications, Kherson State Maritime Academy as an example of Maritime Education and Training Institute employs Quality Management processes and procedures. Quality Standards developed by International Professional Institutions are included for both the students and teachers. Originality. Author analyzes the main peculiarities of monitoring of maritime students` learning outcomes. Conclusion. Monitoring of students` learning outcomes will allow finding optimal ways of training highly skilled and competitive specialists in the maritime sphere in accordance with requirements of maritime documents and techniques required for the modern on board ship management, but also to be prepared for the development of global shipping as a whole.